Some Microbiological and Physico-Chemical Quality of Turkish Sucuk (Sausage) - Siriken, B.; Çadirci, O.; İnat, G.; Yenisey, C.; Serter, M.; Özdemir, M. (Medwell Online, 2009)
In this study, a total of 100 Turkish sucuk samples were analyzed for pysico-chemical and microbiological quality. The maximum levels of moisture, fat and pH limited by Turkish food regulation are 40, 40% Fresh Matter (FM) and 5.8, respectively and sucuk should not contain any starch. In these respects, while 51.5 and 32% of the samples was found high for moisture and pH values, respectively, all the samples were almost suitable for fat value. Starch was detected in 66% of the samples. Lactobacilli and micrococci/staphylococci were <102-108 and <102-107 cfu g-1, respectively. There were negative correlations between Lactobacilli levels and pH values (p<0.01). However, at a few sucuk samples, there were no correlation between Lactobacilli and pH values. NaCl was detected in above 5% Dry Matter (DM) of 25 the samples. Maximum and minimum collagen and hydroxyproline levels were detected in 3.20-9.68 and 0.40-1.21 μg mg-1 (DM), respectively. According to analyzed results, the percentage of moisture, fat, pH, NaCl, starch, collagen and hydroxyproline levels showed variation among the sample analyzed. There is not any official regulation for collagen and hydroxyproline levels of Turkish sucuk. Therefore, this and these kinds of studies may serve as a basis for the preparation of Official Standards of quality for collagen and hydroxyproline content of sucuk in Turkey. © Medwell Journals, 2009.
Keywords: Collagen; Hydroxyproline; Lactobacilli; Micrococci/Staphylococci; Physico-Chemical Quality; Sausage (Sucuk); Starch